PENANGANAN PEKERJA SEKS KOMERSIAL DI INDONESIA - Binahayati Rusyidi; Nunung Nurwati (Universitas Padjadjaran, 2018)
This article describes about the situation of prostitution in Indonesia concerning its types, contributing factors, and elimination strategies using available relevant documents. There are both traditional and contemporary types of prostitution in Indonesia that included sex workers, users and the pimps. The contributing factors of prostitution rooted in three domains including demand, supply and catalyst factors that all associated with social, economic, politic, culture, development of information technology, and globalization factors. Strategies to eradicate prostitution by government in Indonesia rely on the institutional based rehabilitation of sex worker were discussed within the frame of best principles of sex workers rehabilitation. Some limitations were highlighted with regards to the design and implementation of current sex worker’s rehabilitation program.